2006
DOI: 10.1080/14756360500148791
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition kinetics of hydrogen peroxide on β-N-acetyl-d-glucosaminidase from prawn (Penaeus vannamei)

Abstract: The effects of hydrogen peroxide (H 2 O 2 ) on prawn NAGase activity for the hydrolysis of pNP-b-D-GlcNAc have been studied. The results show that H 2 O 2 can reversible inhibit the enzyme (IC 50°0 .85 M) and the inhibition is of a mixed type. The kinetics show that k þ0 is much larger than k 0 þ0 ; indicating the free enzyme is more susceptible than the enzyme-substrate complex in the H 2 O 2 solution. It is suggested that the presence of the substrate offers marked protection against inhibition by H 2 O 2 . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The progress‐of‐substrate reaction method previously described by Tsou (18) and Xie et al (19) was used to study the inhibition kinetics of Zn 2+ on prawn NAGase. The time course of the hydrolysis of the substrate in the presence of different Zn 2+ concentrations was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The progress‐of‐substrate reaction method previously described by Tsou (18) and Xie et al (19) was used to study the inhibition kinetics of Zn 2+ on prawn NAGase. The time course of the hydrolysis of the substrate in the presence of different Zn 2+ concentrations was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The progress‐of‐substrate reaction method previously described by Tsou (18) and Xie et al (19) was applied to the study of the inhibition kinetics of prawn NAGase by Zn 2+ . In this method, 10 μL of enzyme was added to 2.0 mL assay system containing different concentrations of substrate in 0.1 M NaAc‐HAc buffer (pH 5.8) with different concentrations of Zn 2+ .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NCIM 5120. In our previous studies, we reported the purification and some enzymatic characterization of NAGase from prawn (Penaeus vannamei) [14], and the inactivation kinetics of mercuric ion [15], hydrogen peroxide [16], formaldehyde [17] and dioxane [18] on the enzyme has been well studied, respectively. Systematical studies of NAGase from P. vannamei are currently taking place in our laboratory.…”
Section: Introductionmentioning
confidence: 99%